The Role of Field Supervision in Enhancing Worker Engagement and Productivity in Construction Projects - Soekoningrum, Fadila Azzahra Hardiyanti; Djastuti, Indi (Economic and Business Horizon, 2025)
This systematic literature review examines the crucial role of field supervision in enhancing worker engagement and productivity within construction projects. While technological solutions dominate industry improvements, the human aspect of supervision remains understudied despite its significant impact on project outcomes. Through analysis of six key peer-reviewed articles focusing on construction supervision, worker engagement, and productivity published between 2015-2025, this study synthesizes current understanding of effective supervisory practices. Results reveal that successful field supervision depends on three interconnected dimensions: leadership approach, communication effectiveness, and relationship management skills. The findings demonstrate that servant leadership significantly improves both safety compliance and worker engagement, while structured training programs enhance supervisor competencies. The development of measurement tools like PAW-CON represents a notable advancement in quantifying supervisor-worker relationships and identifying workplace psychological factors. The study highlights how technical expertise must be balanced with human-centered leadership skills for optimal supervision outcomes. This review advances both theoretical understanding and practical applications in construction management by providing evidence-based recommendations for developing effective supervisory practices that enhance worker engagement and project productivity.